OPTIMIZING STUDENT ACHIEVEMENT WITH A QUANTUM TEACHING APPROACH - Fauzan Fauzan; Artamin Hairit; Raden Ahmad Muhajir Ansori (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2024)
Problems in learning activities often hinder teachers and students in achieving educational goals. Students' learning difficulties are usually due to the use of inappropriate methods as well as obstacles in providing feedback and improving students' learning skills. This research explores and analyzes the use of Quantum Teaching methods in increasing motivation through a fun and interactive approach. The approach used is descriptive qualitative to provide a detailed description of the use of Quantum Teaching methods in classroom learning. Data were collected from relevant and credible literature sources such as books, scientific articles, newspapers, magazines, and other publications. Content analysis techniques organize information based on relevant themes or categories. This study found that using Quantum Teaching techniques through the TANDUR phase (Grow, Experience, Name, Demonstrate, Repeat, and Celebrate) improved students' cognitive, affective, and psychomotor achievements. Analysis shows that six levels of cognitive learning, five levels of affective activities, and seven stages of psychomotor activities can all be improved by this method. This research provides an in-depth insight into the effectiveness of Quantum Teaching in improving student achievement. The findings provide a basis for educators to adopt more interactive and fun learning strategies and identify factors that influence the effectiveness of this method in the educational context.